Fertility, pregnancy and post partum management after bariatric surgery: a narrative review. Issue 2 (16th January 2022) - Cheah, Sarah; Gao, Yijun; Mo, Shirley; Rigas, Georgia; Fisher, Oliver; Chan, Daniel L; Chapman, Michael G; Talbot, Michael L
Summary: Of the women who gave birth in Australia in 2018, 47% had overweight or obesity, with obesity being associated with both maternal and fetal complications. Bariatric surgery improves fertility and some pregnancy‐related outcomes. Following bariatric surgery, pregnancy should be delayed by at least 12–18 months due to adverse pregnancy outcomes associated with rapid weight loss. Contraception should be prescribed after bariatric surgery, although the effectiveness of the oral contraceptive pill may be reduced due to malabsorption and contraceptive devices such as intrauterine devices should be considered as first line therapy. After bariatric surgery, women should undergo close monitoring for nutritional insufficiencies before, during and after pregnancy. Expert opinion recommends these women undergo dietary assessment and supplementation to prevent micronutrient deficiencies. Bariatric surgeons, bariatric medical practitioners, bariatric dieticians, the patient's usual general practitioner, obstetricians, and maternity specialists should be involved to assist in the multidisciplinary management of these complex patients.